En otra voz : antología de la literatura hispana de los Estados Unidos - Kanellos, Nicolás; Dworkin y Méndez, Kenya; Fernández, José B., 1948-; Gonzales-Berry, Erlinda, 1942-; Lugo-Ortiz, Agnes I.; Tatum, Charles M.; Balestra, Alejandra (Recovering the U.S. Hispanic Literary Heritage Project publication., 2002)
Collects works that represent different aspects of the Spanish-language literary tradition in the United States, including accounts by early explorers and writings by Hispanic Americans, immigrants, and exiles in the United States.